Concise Total Syntheses of the Lycopodium Alkaloids (±)-Nankakurines A and B via Luciduline - Cheng, Xiayun (2010)
[Image: see text] Total syntheses of the Lycopodium alkaloids nankakurines A and B have been accomplished in 6 and 7 steps, respectively, via a sequence that passes through a third Lycopodium alkaloid, luciduline, and forgoes the use of protecting groups on nitrogen. Key features include a short preparation of luciduline followed by a concise and stereoselective aminoallylation/ring-closing metathesis protocol to fashion the spiropiperidine ring common to nankakurines A and B.